(untitled) (Bangladesh Journal of Botany, 2013)
Wide variability was observed for all the characters among 110 lentil accessions. Stem colour varied from normal green (45%) to purple (55%). Prominent and rudimentary tendrils were found in 60% and 40% of the accessions, respectively. Among the characters, flower colour showed the highest variation. White flower colour was observed in 49%, violet in 28%, white with blue veins in 20% accessions and the rest 3% were with blue flowers. Red cotyledon was shown by 90% while with yellow was shown by 10% of the accessions. Green, grey and brown seed coat was observed in 10, 66 and 24% of the accessions, respectively. Seed coat pattern with dots was found in 70% accessions and marbled seed coat pattern was shown by 15.5% while 14.5% did not show any seed coat pattern. DOI: http://dx.doi.org/10.3329/bjb.v41i2.13447 Bangladesh J. Bot. 41(2): 187-190, 2012 (December)